Review of complexity metrics for object oriented software products. - Tieng, Wei Koh; Selamat, Mohd Hasan; Abd Ghani, Abdul Azim; Abdullah, Rusli (International Journal of Computer Science and Network Security (IJCSNS), 2008)
It is widely accepted that sizing or predicting the volumes of various kinds of software deliverable items is one of the first and most dominant aspects of software cost estimating. Most of the cost estimation model or techniques usually assume that software size or structural complexity is the integral factor that influences software development effort. Although sizing and complexity measure is a very critical due to the need of reliable size estimates in the utilization of existing software project cost estimation models and complex problem for software cost estimating, advances in sizing technology over the past 30 years have been impressive. This paper attempts to review the 12 object-oriented software metrics proposed in 90s’ by Chidamber, Kemerer and L.